Preparation, antioxidant and antitumor activities in vitro of different derivatives of levan from endophytic bacterium Paenibacillus polymyxa EJS-3 - Liu, Jun; Luo, Jianguang; Ye, Hong; Zeng, Xiaoxiong (Food and chemical toxicology, 2012)
► Derivatives of levan from Paenibacillus polymyxa EJS-3 were successfully prepared. ► Acetylated (AL), phosphorylated (PL) and benzylated levan (BL) showed high antioxidant activity. ► AL, BL and PL had higher antiproliferative activity in vitro against BGC-823 cells. ► The derivatives could be explored as promising antioxidant and antitumor agents. A levan-type exopolysaccharide (EPS) from Paenibacillus polymyxa EJS-3 was successfully acetylated, phosphorylated and benzylated, respectively, affording its derivatives of acetylated levan (AL), phosphorylated levan (PL) and benzylated levan (BL). Then, the antioxidant and antitumor activities in vitro of the natural polysaccharide and its derivatives were determined. As results, AL, BL and PL all exhibited higher reducing power, scavenging activity against superoxide radical and scavenging activity on hydroxyl radical than the natural polysaccharide, EPS-1. In addition, AL, BL and PL also exhibited higher antiproliferative activity against human gastric cancer BGC-823 cells in vitro than EPS-1. The enhanced activities of the derivatives were probably due to the introduction of acetyl, benzyl, or phosphoryl groups into EPS-1 molecules that increased electron-donating ability and affinity with the receptors on immune cells. The results suggested that the derivatives could be explored as promising antioxidant and antitumor agents.